2022
DOI: 10.1039/d2an00967f
|View full text |Cite
|
Sign up to set email alerts
|

A nanosecond pulsed laser-ablated MWCNT-Au heterostructure: an innovative ultra-sensitive electrochemical sensing prototype for the identification of glutathione

Abstract: Here developed a scheme that aptly describes the reduction of gold nanoparticles' crystalline size on the surface of MWCNT in an aqueous phase to generate LAMWCNT-Au heterostructure, employing a Nd:...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…Lastly, the resulting mixture was put into a Teflon bottle and irradiated for about 30 minutes with 5 minutes irradiation on and 1-minute irradiation off in a 700 Watts microwave oven. 14 After centrifuging for 15 minutes at 8000 rpm, the product was rinsed three times with distilled water followed by one time rinse with ethanol. The solid acquired a brown colouring shortly after spending the night in an 80 °C furnace.…”
Section: Preparation Of Iron Metal-organic Framework (Fe-mof) Nanostr...mentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, the resulting mixture was put into a Teflon bottle and irradiated for about 30 minutes with 5 minutes irradiation on and 1-minute irradiation off in a 700 Watts microwave oven. 14 After centrifuging for 15 minutes at 8000 rpm, the product was rinsed three times with distilled water followed by one time rinse with ethanol. The solid acquired a brown colouring shortly after spending the night in an 80 °C furnace.…”
Section: Preparation Of Iron Metal-organic Framework (Fe-mof) Nanostr...mentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) have the potential to serve as optical sensors, electrochemical sensors, and biosensors. [14][15][16] Several studies were conducted to identify and detect environmental pollutants. 17 Several scholarly evaluations and reports have also been dedicated to utilizing Metal-Organic Frameworks (MOFs) in gas sensing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of cellular and tissue health, it is observed that over 90% of the entire glutathione reservoir is present in its reduced state, known as GSH, while less than 10% is found in the disulfide form, referred to as GSSH. 7 GSH is a crucial cofactor in numerous biological processes, including but not limited to catabolism, drug movement and detoxification. It also plays a vital role in facilitating intercellular communication through gap junctions and acts as a protective agent against the oxidation and cross-linking of protein-SH groups.…”
Section: Introductionmentioning
confidence: 99%